2013
DOI: 10.1016/j.ecolmodel.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Integrating hydraulic, physicochemical and ecological models to assess the effectiveness of water quality management strategies for the River Cuenca in Ecuador

Abstract: Este documento contiene información de prueba. Contáctese con el administrador del Centro para el acceso al documento originar del registro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 47 publications
0
8
1
1
Order By: Relevance
“…Similarly, Dissolved Oxygen (DO) is a variable that in most cases is present to predict the occurrence of macroinvertebrates [51,56,57]. Nonetheless, DO was not a variable of the three GLMs in this research, an observation that was not expected in our research hypothesis.…”
Section: Analysis Of the Explanatory Variables In Relation To Responscontrasting
confidence: 47%
See 1 more Smart Citation
“…Similarly, Dissolved Oxygen (DO) is a variable that in most cases is present to predict the occurrence of macroinvertebrates [51,56,57]. Nonetheless, DO was not a variable of the three GLMs in this research, an observation that was not expected in our research hypothesis.…”
Section: Analysis Of the Explanatory Variables In Relation To Responscontrasting
confidence: 47%
“…In this research, the aforementioned variable is part of the two predictable models for Leptoceridae and Perlidae whereas it is not a factor for the Baetidae model. Interestingly, Holguin-Gonzalez, et al [57] reported the flow velocity as a predictor of the presence of macroinvertebrates in Colombia. In the same way, Ríos-Touma, et al [11] in their research, in the high altitude tropical streams in Ecuador, found that flow velocity had influence in abundance, in communities such as Leptoceridae.…”
Section: Analysis Of the Explanatory Variables In Relation To Responsmentioning
confidence: 99%
“…El ICR considera 17 indicadores, dentro de los cuales se incluyen un índice de integridad biótica de peces, el índice biótico familias de macroinvertebrados de Hilsenhoff (1987) y un índice de géneros de algas. Otro ejemplo es la integración de componentes hidromorfológicos, fisicoquímicos y biológicos en un modelo predictivo desarrollado por Holguin-Gonzalez et al (2013), con el cual se puede prever la ocurrencia de algunos grupos de invertebrados.…”
Section: íNdices Limnológicos En Ríosunclassified
“…These modeling techniques have allowed for the handling of the non-linear behavior of the ecosystem, obtaining models with a high reliability [20][21][22]. In this way, the FC has been associated as one of the explanatory variables describing the presence or absence of some taxa of macroinvertebrates [22][23][24]. Machine learning with different modeling techniques, such as classification trees (CTs) combine reliable classification predictions with transparency, and have been proven to be effective to assess running waters [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The CTs provide good modeling techniques as they focus on the presence/absence or abundance of macroinvertebrate taxa (family or species) in relation to a specific impact or a disturbance in the streams [11,20,[26][27][28]. Consequently, considering the described correlations between fecal coliform presence and macroinvertebrate diversity [18,[22][23][24], compliance to regulatory standards can be simulated based on the prevailing macroinvertebrate community structure by training classification trees on combined observations of fecal coliforms and macroinvertebrates, thereby acting as a proxy indicator for fecal coliform contamination.…”
Section: Introductionmentioning
confidence: 99%